An Implementation Strategic of Environmental, Social and Governance of Waste Materials in the BCG Model from Tobacco, Tobacco Authority of Thailand - Pattpai, Chargarn; Hotrawaisaya, Chattrarat; Aunyawong, Wissawa (The Journal of Development Administration Research, 2025)
Implementing Environmental Social Governance principles for waste materials in the Bio-Circular-Green Economy Model from Tobacco at the Tobacco Authority of Thailand will boost sustainability, improve the organization’s reputation, and favorably impact environmental and social welfare. By implementing waste reduction, recycling, and responsible governance, Tobacco Authority of Thailand can provide a more sustainable and ethical operational framework while promoting a culture of responsibility and accountability. The research instrument was a questionnaire, and it was used for data collection. Key informants included the Deputy Director of the Tobacco Authority of Thailand (Production Division), the Director of Production Division, and the Head of the Bureau of Quality, Safety, and Environment. Descriptive statistics were mean, and standard deviation. The production supervisor must have a minimum of 7 years professional experience in waste material production and management, as well as maximum value addition. The outcomes derived from the SEM (Structural Equation Modeling) investigation are Chi-Square (CMIN) = 58.827, df = 44, p-value = 0.067, RMSEA = 0.028, GFI =0.982, AGFI = 0.951. The purpose of the research was analyzing the ESG performance of waste materials based on the Bio-Circular-Green Economy concept and examine the correlation between ESG development and the performance of the TAOT. Summary of findings; Environmental: Mitigating waste and pollution from tobacco cultivation can alleviate environmental repercussions, including the diminishment of soil and water contamination, Social: Establishing accountability for communities and stakeholders by minimizing waste and pollution, which includes generating employment in the recycling sector or utilizing waste materials, Governance: Enhancing internal systems for transparency and reporting outcomes to stakeholders, so fostering confidence in sustainable operations. Minimizing waste from tobacco manufacturing through a sustainability strategy for waste materials can enhance firms’ ESG outcomes and generate long-term value, encompassing environmental and social responsibility.